Exploring the Influential Power of Parenting Styles on Children’s Development: A Study of Behavioural and Emotional Growth - Dr. Sadia Ayub; Rutaba Qazi; Warda Mahmood; Aqsa Maqbool Abbasi; Tabeer Imtiaz; Hoor Ul Ain (Research Journal of Psychology, 2025)
Parenting styles have a significant impact on children’s emotional regulation and behavioral outcomes. In Pakistan, societal norms often dictate how children are raised, leading parents to impose academic and personal choices on their children due to competition and jealousy. This external pressure not only stifles children’s interests in their academic and life choices but can also cause long-term emotional harm. This study investigates the culturally driven causes of these parenting styles and their effects on children’s cognitive, emotional, and behavioral development. It aims to compare different parenting styles to identify the underlying reasons for the societal neglect of healthy parenting strategies and to assess the psychological consequences that children face. The study utilized a qualitative, exploratory design to gather data from 30 participants, consisting of 10 children and 20 parents. Data collection methods included semi-structured interviews with children, open-ended questionnaires for parents, and direct observation. Thematic analysis revealed that while 42.5% of parents self-identify as authoritative, there are often contradictions between their stated beliefs and their disciplinary actions, which frequently align more closely with authoritarian parenting, particularly under academic stress. Permissive parenting, representing 27.5%, has increased in response to a growing awareness of mental health issues, yet it remains influenced by cultural expectations for high achievement. The findings indicate that many parenting decisions stem from parents’ upbringing and external societal pressures rather than a well-informed understanding of child psychology. This research highlights the need for evidence-based parenting guidance and calls for more academic focus on improving child-rearing practices in Pakistan. By addressing the root causes of emotional neglect and misaligned parenting choices, the study advocates for a shift towards informed parenting strategies to prevent long-term harm to children’s development.